2015
DOI: 10.2337/dc15-0160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Basal-Bolus and Premixed Insulin Regimens in Hospitalized Patients With Type 2 Diabetes

Abstract: OBJECTIVEPremixed insulin is a commonly prescribed formulation for the outpatient management of patients with type 2 diabetes. The safety and efficacy of premixed insulin formulations in the hospital setting is not known.RESEARCH DESIGN AND METHODSIn a prospective, open-label trial, we randomized general medicine and surgery patients to receive a basal-bolus regimen with glargine once daily and glulisine before meals (n = 33) or premixed human insulin (30% regular insulin and 70% NPH insulin) twice daily (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 28 publications
5
60
1
4
Order By: Relevance
“…62 NPH and regular insulin, or premixed (70/30) formulations, demonstrate equivalent blood glucose control when compared to basal bolus regimens, but are associated with higher rates of hypoglycemia in patients with poor oral intake. 64,65 …”
Section: Introductionmentioning
confidence: 99%
“…62 NPH and regular insulin, or premixed (70/30) formulations, demonstrate equivalent blood glucose control when compared to basal bolus regimens, but are associated with higher rates of hypoglycemia in patients with poor oral intake. 64,65 …”
Section: Introductionmentioning
confidence: 99%
“…The results of several randomized controlled trials have shown that treatment with basal-bolus regimens with insulin analogs improves glycemic control and reduces the rate of hospital complications in patients with T2D compared to sliding-scale insulin regimens (911). In addition, the use of basal insulin analogs results in similar glycemic control but in lower rates of hypoglycemia in hospitalized patients with type 1 and type 2 diabetes compared to treatment with NPH (12, 23) and premixed insulin formulations (14). Based on these studies, the use of basal insulin analogs -glargine and detemir- has become the preferred insulin formulations in the hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials using subcutaneous basal-bolus insulin regimens have reported better glycemic control and reduction of complications with this approach compared to sliding-scale insulin in patients with type 2 diabetes (911). Insulin glargine and detemir are the most commonly used basal insulin formulations, and have been associated with lower glycemic variability and less severe hypoglycemia compared to neutral protamine hagedorn insulin (NPH) or premixed insulin formulations (1214). …”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence for using premixed insulin formulations in the outpatient setting (32), a recent inpatient study of 70/30 NPH/regular insulin versus basal-bolus therapy showed comparable glycemic control but significantly increased hypoglycemia in the group receiving premixed insulin (33). Therefore, premixed insulin regimens are not routinely recommended for in-hospital use.…”
Section: Noncritical Care Settingmentioning
confidence: 99%